Preliminary Study about Desalinated Water and Alkalinity - Benouali, Djillali; Benhammadi, Samia; Kherici, Samira; Kadri, Sofiene (International Journal of Scientific Research and Management (IJSRM), 2024)
One of the promising techniques to meet the needs of growing population for drinking water is the desalination of seawater and brackish water. Desalination is carried out mainly by multi-stage flash (MSF) or reverse osmosis (RO).  The water obtained by desalination (RO, MSF and others processes) can be used as drinking water, after the reconstruction of its salts content (blending). However, reverse osmosis can produce, under certain pressure, flow and feed water quality,  water similar in their physic-chemical properties as conductivity, Total Dissolved Salts (TDS) to bottled natural water, widely marketed. In any case, it would be interesting to be able to distinguish reverse osmosis water from sprig water. In this context, the determination of the alkalinity (TA) and the pH and subsequently the verification of the correlation between these two parameters are proposed in this work. Also, a comparison of the physic-chemical quality of drinking water supplied by MSF and RO is made. The parameters, pH, conductivity, TA, TDS and hardness (TH) were discussed. These two types of water are practically identical by physic-chemical quality since the blending is done in the same way by injecting CO2/Calcium carbonate. However, reverse osmosis water contains more sodium chloride because of the low retention rate of membranes against this ion.